The Role of Maternal HP1a in Early Drosophila Embryogenesis via Regulation of Maternal Transcript Production. Issue 1 (15th November 2018) - Park, Ah Rume; Liu, Na; Neuenkirchen, Nils; Guo, Qiaozhi; Lin, Haifan
Abstract: Heterochromatin protein1a (HP1a) is a highly conserved epigenetic factor that associates with heterochromatin in gene silencing. Though it can activate transcription, the function of HP1a in development has been under-investigated..... Heterochromatin protein 1a (HP1a) is a highly conserved and versatile epigenetic factor that can both silence and activate transcription. However, the function of HP1a in development has been underinvestigated. Here, we report the role of maternal HP1a in producing maternal transcripts that drive early Drosophila embryogenesis. Maternal HP1a upregulates genes involved in translation, mRNA splicing, and cell division, but downregulates genes involved in neurogenesis, organogenesis, and germline development, which all occur later in development. Our study reveals the earliest contribution of HP1a during oogenesis in regulating the production of maternal transcripts that drive early Drosophila embryogenesis.